The Influence of Attitudes Towards the Environment and Tax Socialization on Taxpayer Compliance (Case Study at Royal Dental Center) - Angelyne Tan; Tri Wulandari (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine whether Attitudes Towards the Environment and Tax Socialization have a significant effect on Taxpayer Compliance. This study used a quantitative data method and the data source is primary data. The population in this study consists of all visitors at Royal Dental Center. The sample includes Royal Dental Center visitors who possess a Taxpayer Identification Number (NPWP), totaling 33 respondents, selected using incidental sampling data collection techniques. Data analysis and testing consists of validity tests, reliability tests, descriptive statistical tests, classical assumption tests, multiple regression analysis, partial (T test) and simultaneous (F test) hypothesis testing, as well as the coefficient of determination test. The results of analysis prove that Attitudes Towards the Environment doesn’t have significant effect on Taxpayer Compliance with a T count of 1,150 < T table 2,039. Tax Socialization has a partially significant effect on Taxpayer Compliance with a T count of 2,156 > T table 2,039. Attitudes Towards the Environment and Tax Socialization simultaneously have a significant effect on Taxpayer Compliance with a F count of 11,730 > nilai F table 3,32 and regression coefficient value of 43,9%.